Fruit and vegetable intake and the risk of non-alcoholic fatty liver disease: a meta-analysis of observational studies - Wang, Rui; Yan, Ruijuan; Jiao, Junzhe; Li, Feilong; Zhang, Haibo; Chang, Zhanjie; Wei, Hailiang; Yan, Shuguang; Li, Jingtao (Frontiers in Nutrition, 2024)
Purpose This systematic review and meta-analysis of clinical observational studies aims to clarify the correlation between the intake levels of fruits and vegetables and non-alcoholic fatty liver disease (NAFLD). Materials and methods PubMed, Embase, Web of Science, and the Cochrane Library were searched for studies on the association between vegetable or fruit intake with the risk of NAFLD from the foundation of each database up until September 2023. The relative risk (OR) and the 95% confidence interval (CI) were pooled for both the highest and lowest consumption levels of vegetables and fruits to explore their association with the incidence of NAFLD. Results The meta-analysis encompassed 11 studies with a total of 493,682 patients. A higher consumption of vegetables (OR = 0.78, 95% CI = 0.67–0.91) and fruits (OR = 0.88, 95% CI = 0.83–0.93) was found to have a negative correlation with the risk of NAFLD, denoting an inverse association. This correlation, however, varied among different ethnic groups and gender. Conclusions Our results indicate that increased consumption of vegetables and fruits is associated with a reduced likelihood of developing NAFLD. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#searchadvanced, identifier: CRD42023460430.